Process reliabilism and veritic effectiveness - Kardash, Aleksey M. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article discusses the main ideas of Alvin Goldman’s process reliabilism and related epistemological theories. A conceptual distinction between epistemic reliability and veritic effectiveness is introduced as a more parsimonious alternative to traditional arguments against reliabilism. The main ideas of reliabilism are examined in light of the notion of veritic effectiveness.